Toxigenicity of Fusarium isolates and fumonisin B1 contamination in rainy season sorghum (Sorghum bicolor) - DAS, I K; KUMAR, B S VIJAY; RATNAVATHI, C V; KOMALA, V V; ANNAPURNA, A; SEETHARAMA, N (The Indian Journal of Agricultural Sciences, 2010)
Fusarium grain infection and resultant contamination by fumonisins in sorghum [Sorghum bicolor L. (Moench)] grains hamper the quality of rainy season sorghum in enhancing its use as food, feed and value-added products. Laboratory and glasshouse experiments were conducted during 2007 to determine the toxigenicity of Fusarium isolates with respect to fumonisin B1 production on sorghum grains. Field trials were conducted at 4 locations to assess fumonisin B1 contamination in elite sorghum cultivars. Fusarium isolates from different sorghum locations in India showed great variations in their ability to produce fumonisin B1 (range: 0–82 143 μg/kg) on sorghum grain. Four out of 65 isolates (around 6%) were highly toxigenic with ability for fumonisin B1 production both on stored grain (>5 000 μg/kg) as well as on fresh grain (>200 μg/kg) samples. Around 32% of the isolates were non-toxigenic. Morphological characters of the Fusarium isolates and their relation with fumonisin B1 production are discussed. Fumonisin B1 contamination in field samples ranged from 5 to 1 398 μg/kg grain and varied over locations and genotypes. Few genotypes showed toxins below safety limits.